Determination of the effects and optimal thresholds of monetary policy instruments: A study of Central Bank Lending system in Kingdom of Eswatini - Samuel Nkosinathi Dlamini; Pfano Mashau (Cogent Economics & Finance, 2023)
This paper examines the impact of monetary policy instruments such as discount rate, reserve requirement and liquidity requirement on bank credit to the private sector in the Kingdom of Eswatini. Monthly data sourced from the Central Bank of Eswatini and Eswatini Central Statistics Office is used for the period January 2000 to December 2017. Using the Johansen cointegration test and Vector Error Correction Model, our results show that: there is one cointegration in the model and the current levels of the discount rate, reserve requirement and liquidity requirement bear a negative and significant effect to bank credit to the private sector. This indicates that the three instruments are not supportive to economic growth and they are not optimal to stimulate credit. Applying the Quadratic approach, findings of this study reveal that the optimal monetary policy mix (thresholds) to stimulate bank credit to the private sector while maintaining inflation within reasonable levels is 5.42% for the discount rate, 4.03% for the reserve requirement, 12.48% for the liquidity requirement. The study recommends that the Central Bank of Eswatini should always take into account the existence of trade-off in monetary policy instruments results in order to stimulate bank lending to the private sector.
Keywords: 330; bank lending; discount rate; Johansen cointegration approach; liquidity requirement; Quadratic model; reserve requirement